Once a Soldier, Always a Dependent - Sommers, Christina Hoff (The Hastings Center report, 1986)
Why are veterans entitled to special benefits, such as free medical care? Not because such a benefit is an inducement to military service, or because a soldier accepts risk. Rather, the relationship of the Army, to use one service as an example, to a soldier is like that of a parent to a child. The right to health care, even carried beyond the term of service, is an extension of this quasi-familial relationship.